2022
DOI: 10.1039/d1ra08413e
|View full text |Cite
|
Sign up to set email alerts
|

High performance and remarkable cyclic stability of a nanostructured RGO–CNT-WO3 supercapacitor electrode

Abstract: One of the most pressing concerns in today's power networks is ensuring that consumers (both home and industrial) have access to efficient and long-lasting economic energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In comparison, the rGO electrode exhibits a capacitance retention of approximately 91.99% under the same scan rate conditions. These higher values of capacitance retention signify that a material excels at preserving its capacitance, a quality often sought after in applications related to energy storage or supercapacitors [47].…”
Section: Electrochemical and Bio-sensor Studiesmentioning
confidence: 99%
“…In comparison, the rGO electrode exhibits a capacitance retention of approximately 91.99% under the same scan rate conditions. These higher values of capacitance retention signify that a material excels at preserving its capacitance, a quality often sought after in applications related to energy storage or supercapacitors [47].…”
Section: Electrochemical and Bio-sensor Studiesmentioning
confidence: 99%
“…They observed that the SC of the supercapacitor was 440 F/g with 98% coulombic efficiency after 5000 cycles. A study investigated a supercapacitor constructed by the tungsten trioxide (WO 3 )/CNT/RGO electrode and demonstrated the SC of 691.38 F/g at 5 mV/s [71]. Ngo et al [72] fabricated polydopamine/CNT/graphene oxide nanocomposites as the flexible symmetric electrode for the supercapacitor and demonstrated the SC of 217.4 F/g.…”
Section: Introductionmentioning
confidence: 99%
“…Vanadium pentoxide (V 2 O 5 ), as a layered transition metal oxide, possesses a unique valence electron structure and is rich in a variety of compound states (þ5, þ4, þ3, þ2), enabling it to exhibit a high specific capacitance and the potential to enhance the capacitance properties of WO 3 when combined. [47][48][49][50] In this study, we employed a simple hydrothermal-calcination method to incorporate a V 2 O 5 precursor solution into presynthesized WO 3 nanorods. By investigating the influence of the precursor (V 2 O 5 ) concentration on the morphology and performance of the composite, we identified the optimal concentration and successfully prepared a 3D network-like WO 3 /V 2 O 5 /CC composite material.…”
Section: Introductionmentioning
confidence: 99%
“…Vanadium pentoxide (V 2 O 5 ), as a layered transition metal oxide, possesses a unique valence electron structure and is rich in a variety of compound states (+5, +4, +3, +2), enabling it to exhibit a high specific capacitance and the potential to enhance the capacitance properties of WO 3 when combined. [ 47–50 ]…”
Section: Introductionmentioning
confidence: 99%